The Role of Location-Related Factors in U.S. Banking Involvement Abroad: An Empirical Examination - Nigh, Douglas; Cho, Kang Rae; Krishnan, Suresh (Journal of International Business Studies, 1986)
This study examines the role of major location-specific advantages in the international branch banking involvement of U.S. banks. Using pooled time-series (1976-82), cross-sectional (thirty countries) regression analysis, this study finds that the U.S. business presence in foreign country has a strong positive effect on U.S. branch banking activity in that country. In contrast, the local market opportunity appears to have no significant effect. These results hold for the entire set of countries, as well as each of five subsets (developed, less developed, European, Latin American, and Asian countries). The openness of the host country to the establishment of new foreign bank branches does affect U.S. branch banking involvement. This effect is most pronounced in the less developed countries, particularly those in Asia.